2021
DOI: 10.1002/ejhf.2355
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial on the short‐term effects of 12‐week sacubitril/valsartan vs. enalapril on peak oxygen consumption in patients with heart failure with reduced ejection fraction: results from the ACTIVITY‐HF study

Abstract: ACTIVITY-HF was a randomized, double-blind, active-controlled study, which assessed the short-term effect of sacubitril/valsartan compared with the active comparator enalapril on improving maximal exercise capacity in patients with heart failure with reduced ejection fraction (HFrEF).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 32 publications
2
34
0
Order By: Relevance
“…ACTIVITY‐HF is a randomized controlled trial that enrolled 201 patients with HFrEF and aimed at comparing the effects of sacubitril/valsartan versus enalapril on exercise capacity. The primary endpoint of change from baseline to 12 weeks in peak oxygen consumption did not differ between groups 7 . Results are consistent with previous findings form the OUTSTEP‐HF trial 8 …”
Section: Guideline‐directed Medical Therapysupporting
confidence: 90%
“…ACTIVITY‐HF is a randomized controlled trial that enrolled 201 patients with HFrEF and aimed at comparing the effects of sacubitril/valsartan versus enalapril on exercise capacity. The primary endpoint of change from baseline to 12 weeks in peak oxygen consumption did not differ between groups 7 . Results are consistent with previous findings form the OUTSTEP‐HF trial 8 …”
Section: Guideline‐directed Medical Therapysupporting
confidence: 90%
“…A blockade showed positive effects on the ventricular geometry, morbidity and mortality in HFrEF [14]. Interestingly, no short-term effect on maximal exercise capacity could be proven [15]. With ischemia and hypertension as leading causes of CHF in general, a positive in uence of a blockade of the renin-angiotensin-aldosterone system on cardiac remodeling could be assumed independently of the ejection fraction.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed characteristics of 16 studies (10,19,20,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) are shown in Table 1. Most of the data are come from ClinicalTrials.gov, 14 trials are multi-center and 12 trials are aimed at patients with HF.…”
Section: Study Characteristicsmentioning
confidence: 99%